In vivo Modeling and Molecular Characterization: A Path Toward Targeted Therapy of Melanoma Brain Metastasis - Gaziel-Sovran, Avital; Osman, Iman; Hernando, Eva (Frontiers in Oncology, 2013)
Brain metastasis from melanoma remains mostly incurable and the main cause of death from the disease. Early stage clinical trials and case studies show some promise for targeted therapies in the treatment of melanoma brain metastasis. However, the progression-free survival for currently available therapies, although significantly improved, is still very short. The development of new potent agents to eradicate melanoma brain metastasis relies on the elucidation of the molecular mechanisms that drive melanoma cells to reach and colonize the brain. The discovery of such mechanisms depends heavily on pre-clinical models that enable the testing of candidate factors and therapeutic agents in vivo. In this review we summarize the effects of available targeted therapies on melanoma brain metastasis in the clinic. We provide an overview of existing pre-clinical models to study the disease and discuss specific molecules and mechanisms reported to modulate different aspects of melanoma brain metastasis and finally, by integrating both clinical and basic data, we summarize both opportunities and challenges currently presented to researchers in the field.